A Lipocalin-Derived Peptide Modulating Fibroblasts and Extracellular Matrix Proteins - Linda Christian Carrijo-Carvalho; Durvanei A. Maria; Janaina S. Ventura; Kátia L. P. Morais; Robson L. Melo; Consuelo Junqueira Rodrigues; Ana Marisa Chudzinski-Tavassi (Journal of Toxicology)
Lipocalin family members have been implicated in development, regeneration, and pathological processes, but their roles are unclear. Interestingly, these proteins are found abundant in the venom of the Lonomia obliqua caterpillar. Lipocalins are β-barrel proteins, which have three conserved motifs in their amino acid sequence. One of these motifs was shown to be a sequence signature involved in cell modulation. The aim of this study is to investigate the effects of a synthetic peptide comprising the lipocalin sequence motif in fibroblasts. This peptide suppressed caspase 3 activity and upregulated Bcl-2 and Ki-67, but did not interfere with GPCR calcium mobilization. Fibroblast responses also involved increased expression of proinflammatory mediators. Increase of extracellular matrix proteins, such as collagen, fibronectin, and tenascin, was observed. Increase in collagen content was also observed in vivo. Results indicate that modulation effects displayed by lipocalins through this sequence motif involve cell survival, extracellular matrix remodeling, and cytokine signaling. Such effects can be related to the lipocalin roles in disease, development, and tissue repair.